ISSUES OF ENSURING THE LEGAL STATUS OF A LAWYER IN CRIMINAL PROCEEDINGS (Journal of actual problems of jurisprudence, 2026)
The professional activity of a lawyer, who is constitutionally obligated to provide legal assistance to everyone, plays a vital role in protecting human and civil rights and freedoms. This constitutional obligation is fulfilled through the practice of a specific type of legal activity within its procedural framework. The relevance of this research lies in its exploration of the procedural status of legal activity performed by a lawyer. This, on the one hand, allows for a more detailed analysis of the status of lawyers when providing legal assistance to their clients in various types of procedural proceedings, and on the other, distinguishes their legal status from that of other individuals providing legal services.The special legal status of a lawyer in pre-trial investigation and criminal proceedings is linked to their professional and procedural status. The role and responsibilities of a lawyer in criminal proceedings reflect both the moral, intellectual, and spiritual development of society itself, as well as the degree of democracy in the state, the status of the individual within it, their rights, freedoms, interests, and their protection. The procedural status of a lawyer in criminal proceedings is the provision of legal assistance to a client in determining and realizing their rights, freedoms, and legitimate interests, that is, in representing them during the preliminary investigation and defending them in court using legal means and methods.In summing up the results of the study, the authors make a number of proposals aimed at improving the legal framework for the exercise of attorneys' powers in criminal proceedings, namely, amending the Criminal Procedure Code of the Republic of Kazakhstan to develop and clarify attorneys' powers to collect evidence, as well as unifying investigative actions and operational-search measures that limit the constitutional rights of citizens, and regulating this issue in criminal procedure legislation.Key words: advocacy, legal status, criminal proceedings, professional defense, professionalism, procedural status of a lawyer in pre-trial investigation.